2005
DOI: 10.1016/j.foodhyd.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A chitosan–gelatin blend as a coating for fish patties

Abstract: A coating made in cold from a blend of a chitosan and a gelatin solution was applied to patties made of chilled cod, and its preservative effect was assessed by colour measurements, rheological measurements (hardness, elasticity, cohesiveness, chewiness, gumminess, and adhesiveness), biochemical determinations (total volatile bases and thiobarbituric acid as measures of rancidity) and microbiological assays (total bacterial counts, luminiscent bacteria, enterobacteria, pseudomonas, lactic acid bacteria, and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(131 citation statements)
references
References 24 publications
6
122
0
3
Order By: Relevance
“…The antimicrobial properties of chitosan coating have been reported in the literature López-Caballero et al, 2005). Jeon et al (2002) described how bacterial growth (total counts on plate count agar at 20ºC) reached the stationary phase in all chitosan-coated cod and herring samples after 6 days, and also how there was a reduction of up to three log cycles between coated samples and controls after 12 days of chilled storage.…”
Section: Edible Film and Coatingmentioning
confidence: 96%
See 1 more Smart Citation
“…The antimicrobial properties of chitosan coating have been reported in the literature López-Caballero et al, 2005). Jeon et al (2002) described how bacterial growth (total counts on plate count agar at 20ºC) reached the stationary phase in all chitosan-coated cod and herring samples after 6 days, and also how there was a reduction of up to three log cycles between coated samples and controls after 12 days of chilled storage.…”
Section: Edible Film and Coatingmentioning
confidence: 96%
“…Jeon et al (2002) described how bacterial growth (total counts on plate count agar at 20ºC) reached the stationary phase in all chitosan-coated cod and herring samples after 6 days, and also how there was a reduction of up to three log cycles between coated samples and controls after 12 days of chilled storage. López-Caballero et al (2005) reported that a coating consisting of a blend of chitosan dissolved in acetic acid and gelatine exerted an inhibitory effect on the gram-negative flora of fish patties. Various factors affect the antimicrobial action of chitosan and its mechanism of action appears to be related to interactions between the positively charged chitosan molecules and the negatively charged microbial cell membrane (Shahidi et al, 1999) as well as to its function as a barrier against oxygen transfer .…”
Section: Edible Film and Coatingmentioning
confidence: 99%
“…The use of chitosan as an antimicrobial material for food has been widely reported, for example, in bread , seafood (Tsai et al, 2002;López-Caballero et al, 2005), fruit and vegetables (Chien et al, 2007;Badawy and Rabea, 2009), meat (Sagoo et al, 2002;Rao et al, 2005), sausage (Lin and Chao, 2001;Soultos et al, 2008) and dairy products (Suman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nowzari et al (2013) found that rainbow trout coated with gelatin based films and stored refrigerated for 16 days has lower TBARS values than controls. However, Lopez-Caballero, Gomez-Guillen, Perez-Mateos, and Montero (2005) observed that gelatin coatings have no influence on lipid oxidation of cod fillets stored at 2°C for 15 days. Besides this, in the present work, for coated samples with FGF it seemed that the increase was generally smaller (results not showed), however, there were no statistically significant differences (ANOVA, LSD test; p > 0.05) supporting that conclusion.…”
Section: Chemical Variationsmentioning
confidence: 93%